2014
DOI: 10.14742/ajet.322
|View full text |Cite
|
Sign up to set email alerts
|

Class blogs as a teaching tool to promote writing and student interaction

Abstract: <p>Blogs are a useful teaching tool for improving student writing and increasing class interaction. However, most studies have looked at individual blogs rather than blogs maintained by a whole class. We introduced assignments involving participation in class blogs to four science communication classes with enrolments of between 15 and 36 students. We administered paper-based surveys to obtain student perceptions of the value of the blogging assignment. Based on feedback in semester one, we increased com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…In higher education, social media-based CoPs can enhance social learning opportunities and students' sense of community (Hung and Yuen 2010;Sullivan and Longnecker 2014) as well as provide a valuable forum for sharing local knowledge (Gray 2004). Social media-based CoPs add particular value for distance learners or a dispersed group of students (Mayes and de Freitas 2007), newcomers (Gray 2004), and those engaged in self-directed learning (McLoughlin and Lee 2010;Gray 2004).…”
Section: Community Of Practicementioning
confidence: 99%
“…In higher education, social media-based CoPs can enhance social learning opportunities and students' sense of community (Hung and Yuen 2010;Sullivan and Longnecker 2014) as well as provide a valuable forum for sharing local knowledge (Gray 2004). Social media-based CoPs add particular value for distance learners or a dispersed group of students (Mayes and de Freitas 2007), newcomers (Gray 2004), and those engaged in self-directed learning (McLoughlin and Lee 2010;Gray 2004).…”
Section: Community Of Practicementioning
confidence: 99%
“…They demonstrated that social media with appropriate training provides opportunities for students to improve self-regulation; however, their study was conducted with an individual task. Very few empirical studies have been conducted with a collaborative project to examine how social media support students' self-regulation and co-regulation (Philip & Nicholls, 2009;Sullivan & Longnecker, 2014). In addition, Cho and Cho (2013) did not examine students' experience with social media, critical for further integration of technology in the classroom (Sullivan & Longnecker, 2014).…”
Section: Social Mediamentioning
confidence: 99%
“…Very few empirical studies have been conducted with a collaborative project to examine how social media support students' self-regulation and co-regulation (Philip & Nicholls, 2009;Sullivan & Longnecker, 2014). In addition, Cho and Cho (2013) did not examine students' experience with social media, critical for further integration of technology in the classroom (Sullivan & Longnecker, 2014). We therefore sought to determine whether social media are helpful in enhancing not only students' self-and co-regulation in collaboration but also experiences with regulation activities embedded in social media in a collaborative project.…”
Section: Social Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…Still, some investigate blog language, such as Doodstar's (2004) study of vulgarity in a blog controversy with a particular linguistic focus and Fellner and Apple's (2006) study of word frequencies in university level language learner's blogs in a developmental perspective. Some studies explicitly investigate how the blog impacts writing in academic settings, investigating the blog's affordances for various ways of collaborative writing and peer comments, for writing drafts and as a tool for scaffolding during writing instruction (Wong & Hew, 2010, Chen, Liu, Shih, Wu, & Yuan, 2011Sullivan & Longnecker, 2014;Novakovich, 2016;). Findings were that comments from peers improved the quality of writing, the students took a positive attitude towards giving and receiving feedback (Chen et al, 2011), and the feedback on the blog was perceived as more critical and directive than feedback in traditional settings, correlating positively with the quality of the writing (Novakovich, 2016).…”
Section: Introductionmentioning
confidence: 99%